Evaluation of a natural S‐equol supplement in treating premenstrual symptoms and the effect of the gut microbiota: An open‐label pilot study - Takashi Takeda; Yasutaka Chiba (Wiley, 2022)
Abstract Aim Premenstrual syndrome causes disturbances in many women's daily activities. Isoflavones might cause changes in the estrogen cycle by their selective estrogen receptor modulator‐like activities. Equol, which is a metabolite of a soy isoflavone, has greater biological activity than other soy isoflavones. In this preliminary study, we aimed to examine the effect of a natural S‐equol supplement (SE5‐OH) on premenstrual symptoms. The gut microbiota has recently been suggested to play an important role in brain function in psychiatric disease, such as depression. Therefore, we further aimed to evaluate the relationship of the effect of SE5‐OH and the gut microbiota at preintervention. Methods Twenty women who showed premenstrual symptoms and were nonequol producers were enrolled in an open‐label, single‐arm, clinical study in which they received oral SE5‐OH for two period cycles. The Daily Record of Severity of Problems (DRSP) total score was evaluated during the intervention cycles. Before taking SE5‐OH, fecal samples were obtained and subjected to terminal restriction fragment length polymorphism analysis. Results The response rate to treatment (≥50% reduction from baseline in the DRSP total score) was 10.5%. Post hoc analysis showed a significant improvement in the change in the DRSP total score (P = .008) and DRSP scores for four core premenstrual dysphoric disorder symptoms. Multiple regression analysis showed that the percentage improvement of the DRSP total score was positively related to Bifidobacterium and negatively related to Clostridium cluster IV. Conclusion SE5‐OH supplementation may be an acceptable treatment for premenstrual symptoms. The intestinal microbiota may have an effect on SE5‐OH.